Modelling bilingual / multilingual acquisition - Medved Krajnović, Marta (2009)
Intensive search for the 'best' theoretical model to explain second language acquisition process has been going on for at least 30 years and is still continuing. Various models have been offered, with the majority of them focusing on one or some aspects of the acquisition process, or one particular language subsystem or skill, while neglecting the others. Furthermore, a rather neglected or isolatedly approached area was the process of language attrition, that is a changing competence in a language user's L1 under the influence of L2, or a loss of competence in any non-native language due to a change in an individual's linguistic environment. However, during the last decade models that try to embrace formalist, functionalist and alternative perspectives, as well as shed light on complex multidirectional interaction of language systems in bilingual or multilingual development are gaining ground (e.g. Sharwood Smith and Truscott's (2005) MOGUL framework (2005), Herdina and Jessner's DMM (2002)). Moreover, a view of a bilingual or a multilingual person as a specific, multicompetent speaker / hearer who differs from his or her monolingual peers in both L1 and L2 (and L3) competence has established itself (Grosjean 1989, Cook 2002, 2003, Schmid and Kopke 2007) In this presentation the focus will be on trying to present the complexity of a bilingual and subsequently multilingual development in a visual form. Figures and graphs encompassing linguistic development of first bilingual and then multilingual subject will be presented. The aim is to shed light on the mutual interaction (on the phonological, morphosyntactic, semantic and pragmatic levels) among the subjects languages. Particular stress will be put on the very dynamic power relationship between the subject's L1 and L2, and as well as his L3 and L4 on both the production and comprehension level. The goal is also to present the overall tendency of the subject's multilingual development relying mostly on the concept of multicompetence (Cook 2002), thresholds theory (Cummins 1979) and dynamic system's theory (de Bot et al. 2007). The data for the presentation have been collected during an on-going case-study of a boy who started his linguistic development as a monolingual speaker of Croatian (L1). At the age of 3 years he started acquiring English in a natural context (Ireland) as his L2 and by the age of 5, English (L2) became the boy's primary linguistic system, at least at the level of language production. The power relationship between the subject's L1 and L2 changed again upon his return to his home country (Croatia), and further dynamism was added when the boy started learning French as his first foreign language. At the age of 9 years, the boy moved to Japan where intensive development of his L2 (English) started again, as well as intensive learning of Japanes as his second foreign language. These different contexts of the subject's bilingual / multilingual development will be labelled as stage 1 (subject aged 3 – 5, country of residence – Ireland), stage 2 (subject aged 5 – 9, country of residence – Croatia) and stage 3 (subject aged 9 – 11, country of residence – Japan). The method of data collection during the course of the study has been four-fold: the mother's (= researcher's) diary ; audio and video recordings of the subject's spontaneous communication in a variety of contexts ; language learner's portfolio and other parties' observation (e.g. teachers') of the boy's cpmmunicative and linguistic development. In presenting the data, particular stress will be put on the qualitative and quantitative differences between the intensive linguistic changes (especially in terms of L1 attrition and L2 acquisition / re-acquistion) that happened during the first and third stage of the subject's bilingual / multilingual development. The model within which the data will be graphically presented and interpreted is Dynamic Model of Multilingualism (DMM). The explanation for the qualitative and quantitative differences in the subject's bilingual / multilingal development between stages one and stage three will be primarily based on the age factor (especially on the role of the age in the linguistic entranchement and metalinguistic maturity), previous language learning experience and language maintenance effort factors.
Projekt MZOS
ENG